2002
DOI: 10.2307/3069321
|View full text |Cite
|
Sign up to set email alerts
|

Participative Decision Making and Employee Performance in Different Cultures: The Moderating Effects of Allocentrism/Idiocentrism and Efficacy.

Abstract: The relationship between perceived participative decision making and employee performance was examined in matched samples of employees from the Hong Kong and U.S. branches of one organization. Self-efficacy in regard to participating in decisions and idiocentrism moderated the relationship between perceived participative decision-making opportunity and individual performance. Perceptions of the participation efficacy of a work unit and allocentrism moderated the relationship between participative decision-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(107 citation statements)
references
References 30 publications
1
103
0
3
Order By: Relevance
“…These appear to be critical factors in achieving TMT behavioral integration (Simsek et al, 2005). Other research has found that empowering employees produces better outcomes (Field & House, 1990;Lam et al, 2002;Stewart, 2006;Wagner, 1994), and the improvement of team processes strengthened the empowerment-performance relationship (Spreitzer et al, 1999). Specific factors that have been found to be influenced by team empowerment include knowledge sharing (Srivastava et al, 2006), team efficacy (Srivastava et al), and groups' capacities to cope with complex issues (Koopman & Wierdsma, 1998;Scully et al, 1995;Vroom & Yetton, 1973).…”
Section: Theoretical Implicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…These appear to be critical factors in achieving TMT behavioral integration (Simsek et al, 2005). Other research has found that empowering employees produces better outcomes (Field & House, 1990;Lam et al, 2002;Stewart, 2006;Wagner, 1994), and the improvement of team processes strengthened the empowerment-performance relationship (Spreitzer et al, 1999). Specific factors that have been found to be influenced by team empowerment include knowledge sharing (Srivastava et al, 2006), team efficacy (Srivastava et al), and groups' capacities to cope with complex issues (Koopman & Wierdsma, 1998;Scully et al, 1995;Vroom & Yetton, 1973).…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…Although there is considerable debate and disagreement about whether employee participation enhances firm performance (Cotton et al, 1988;Locke & Schweiger, 1979), there is consistent evidence that employees who participate in making decisions perform better (Field & House, 1990;Lam, Chen, & Schaubroeck, 2002), as do groups and teams that are led by more empowering leaders (Stewart, 2006;Wagner, 1994). Stewart's (2006) meta-analysis found that, on average, the effect of empowering leadership on team performance was as strong as the effect of transformational leadership on team performance.…”
Section: Ceo Empowering Leadership Tmt Behavioral Integration and Tmentioning
confidence: 93%
“…Klassen, 2004;Pajares, 2007) suggest that psychological processes are contingent on cultural factors. For example, cultural dimensions related to constructions of individualism and collectivism seem to encourage participants from Asian cultures to exhibit lower self-efficacy beliefs than those who are not from these cultures, but these diminished self-efficacy beliefs do not impede their performance (Ho & Hau, 2004;Lam, Chen, & Schaubroeck, 2002;Leung, 2001;Salili, Chiu, & Lai, 2001). Self-efficacy beliefs are generally more other-oriented than self-oriented for people in non-Western cultures (Earley, Gibson, & Chen, 1999;Kim & Park, 2006).…”
Section: A Selective Review Of Some Relevant Studiesmentioning
confidence: 95%
“…The training scale was adopted from [13]. A 7 five point scale of hard skills was adopted from [29]. The study population consisted of 399 employees working in the PNA organizations.…”
Section: Methodsmentioning
confidence: 99%